1992
DOI: 10.1111/j.1365-2796.1992.tb00583.x
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia, iron‐related measurements and erythropoietin levels in untreated patients with active leprosy

Abstract: The mechanisms responsible for anaemia in leprosy were studied prior to the institution of therapy in 56 patients with active disease. Haematological indices, iron-related measurements, inflammatory markers and erythropoietin levels were assessed, with bone-marrow studies being performed on anaemic patients. Anaemia was more common in the patients with lepromatous leprosy (85.7%) than it was in the rest of the group (19%). The lepromatous group exhibited the disordered iron transport of the anaemia of chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
(4 reference statements)
1
5
0
1
Order By: Relevance
“…Lapinsky et al (1992) reported the occurrence of anaemia in MB patients and classified this anaemia as AI on the basis of decreased serum iron levels and mild increases in serum ferritin concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lapinsky et al (1992) reported the occurrence of anaemia in MB patients and classified this anaemia as AI on the basis of decreased serum iron levels and mild increases in serum ferritin concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Anaemia is a common finding in patients presenting with MB leprosy (Sher et al 1981, Lapinsky et al 1992, Jain et al 1995, Rea 2001. However, the exact mechanism underlying the reduction in serum iron and the effect of reduced iron levels on leprosy are not well understood.…”
mentioning
confidence: 99%
“…99 Lipid antigens are responsible for false positive reactions for syphilis. 100 The concentration of C-reactive protein is significantly high in patients with ENL and arthritis compared to those without arthritis.…”
Section: Imaging Testsmentioning
confidence: 99%
“…Gangguan terhadap respon eritropoietin tampaknya menjadi faktor dominan sebagai patogenesis terjadinya anemia pada kelompok ini. 19 Dari seluruh faktor risiko yang diteliti hanya lama terapi ≥3 bulan yang bermakna terhadap terjadinya anemia. Penelitian sebelumnya melaporkan onset anemia terjadi saat 3 bulan awal terapi.…”
Section: Pembahasanunclassified